2010
DOI: 10.1007/s11883-010-0105-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Smoking Cessation in the Prevention of Coronary Artery Disease

Abstract: Smoking (tobacco addiction) is the most significant of the modifiable cardiovascular risk factors. Mistakenly described as a "habit" or "behavioral choice," the onset of tobacco addiction quickly follows the acquisition of an ability to inhale cigarette smoke and is reflected in a transformation of neurophysiologic function and nicotine-receptor density. Thereafter, comfort and a degree of neurophysiologic "equanimity" require the regular administration of nicotine. Smokers inhale thousands of other chemicals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 49 publications
0
17
0
6
Order By: Relevance
“…In particular, BC is a smokingrelated disease, and many patients with BC have a long smoking history [6,7]. As is very well known, smoking also causes other cancers (most notably lung) as well as cardiovascular disease [8]. Other environmental exposures may also contribute to the development of BC and other diseases simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, BC is a smokingrelated disease, and many patients with BC have a long smoking history [6,7]. As is very well known, smoking also causes other cancers (most notably lung) as well as cardiovascular disease [8]. Other environmental exposures may also contribute to the development of BC and other diseases simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Endothelial cells and circulating monocytes are key players in the inflammatory response leading to the formation of atherosclerotic plaques, a process known to be accelerated by CS (Pipe et al, 2010). In vivo studies have shown that CXCL12 induces monocyte chemotaxis into injured tissues (Blades et al, 2002;Zhang et al, 2011) and mediates homing of stem/progenitor cells and bone marrow-derived monocytes (Ceradini et al, 2004;Doring et al, 2014;Hill et al, 2004).…”
Section: Cs Causes Cardiovascular Disease (Centers For Disease Contromentioning
confidence: 99%
“…Smoking cessation is associated with 36-50% reduction in morbidity and mortality in CHD patients, with the benefits of quitting smoking outperforming those related to other preventive strategies such as blood pressure or cholesterol control (2,3). Cessation is especially crucial in this population, as continuing to smoke renders such secondary prevention interventions less efficacious (7,8), therefore smokers are not deriving the full benefit from preventive therapies.…”
Section: Introductionmentioning
confidence: 99%